Traditions Of The Mushoara Genre In The Works Of Sayfi Sarayi - Abdurahmonova Mohinur (International Journal Of Literature And Languages, 2026)
Literature is one of the highest manifestations of human thought, aesthetic sensibility, and spiritual life. In the cultural heritage of every nation, literature occupies a special place, and classical literature, in particular, represents an invaluable treasury. Among the various genres formed within classical literature, the mushoara genre stands out for its distinctive artistic and aesthetic features, its spirit of creative competition, and its high regard for poetry. This genre served not only as a means for poets to demonstrate their artistic mastery, but also as a platform for testing the depth of their thought, richness of vocabulary, level of literary knowledge, and creative potential. Mushoara gatherings were commonly held at literary assemblies, royal courts, and creative circles, and they were regarded as significant cultural events of their time. This article examines the role and artistic-aesthetic characteristics of the mushoara genre in the works of Sayfi Sarayi, one of the prominent representatives of fourteenth-century classical Turkic literature. In the course of the study, the formal and thematic features of the genre are analyzed through examples of mushoaras included by Sayfi Sarayi in his translation of Saʿdi Shirazi’s Gulistan. In particular, the use of poetic devices such as meter, rhyme, radif, simile, metaphor, and tajnis, as well as the harmony of mystical and amorous themes in mushoaras conducted with poets such as Mawlana Qazi Muhsin, Mawlana Ishaq, Mawlana Imad Mawlavi, and Ahmad Khoja al-Sarayi, is examined on a scholarly basis. The article reveals the role of the mushoara genre in fostering creative competition, literary dialogue, and the continuity of artistic traditions. The findings demonstrate that Sayfi Sarayi’s mushoaras constitute an important source reflecting the literary milieu of the fourteenth century and play a significant role in the development of the mushoara genre within classical Turkic literature.